Comparative Evaluation of Focused Retrieval 9th International Workshop of the Inititative for the Evaluation of XML Retrieval, INEX 2010, Vugh, The Netherlands, December 13-15, 2010, Revised Selected Papers - Geva, Shlomo; Kamps, Jaap.; Schenkel, Ralf.; Trotman, Andrew; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the thoroughly refereed post-workshop proceedings of the 9th International Workshop of the Initiative for the Evaluation of XML Retrieval, INEX 2009, held in Vught, The Netherlands, in December 2009. The aim of the INEX 2010 workshop was to bring together researchers in the field of XML IR who participated in the INEX 2010 campaign. During the past year, participating organizations contributed to the building of large-scale XML test collections by creating topics, performing retrieval runs and providing relevance assessments. The workshop concluded the results of this large-scale effort, summarized and addressed issues encountered, and devised a work plan for the future evaluation of XML retrieval systems. The 37 full papers presented were carefully reviewed and selected from 42 submissions; they are organized into sections corresponding to the nine tracks of the workshop, investigating various aspects of XML retrieval, from book search to entity.
Keywords: Computer science; Data structures (Computer science).; Database management; Information storage and retrieval systems; Computer Science; Information Storage and Retrieval; Database Management; Data Structures